Apremilast: A Phosphodiesterase 4 Inhibitor for the Treatment of Psoriatic Arthritis - Mease, Philip J. (Rheumatol Ther, 2014)
INTRODUCTION: Psoriatic arthritis (PsA) is a spondyloarthritis that occurs in up to 30% of psoriasis patients. Patients with PsA are at risk for decreased quality of life due to both joint and skin symptoms, impaired physical function and disease progression. Treatments include non-steroidal anti-inflammatory drugs, conventional systemic disease-modifying anti-rheumatic drugs (DMARDs) such as methotrexate, and biologic agents, including tumor necrosis factor-α inhibitors. The most recently introduced treatment option is apremilast, an oral phosphodiesterase 4 inhibitor. METHODS: This review provides an in-depth discussion of apremilast’s mechanism of action, and evidence of its clinical efficacy and safety from the Psoriatic Arthritis Long-term Assessment of Clinical Efficacy (PALACE) phase III pivotal clinical trials (PALACE 1, 2, and 3). RESULTS: These trials demonstrate that apremilast is effective for the treatment of active PsA, despite prior conventional DMARDs or biologic treatment. The primary efficacy end point, a 20% improvement from baseline in modified American College of Rheumatology response criteria at Week 16, was achieved by significantly greater proportions of patients treated with apremilast 20 mg twice daily (BID) and apremilast 30 mg BID versus placebo in PALACE 1, 2, and 3. Improvements in this and other clinical and patient-reported end points, including swollen and tender joint counts, Psoriasis Area and Severity Index score, physical function, and quality of life, were maintained, extending over 52 weeks of treatment among patients initially randomized to apremilast. Apremilast’s safety profile has been acceptable, with diarrhea and nausea being the most common adverse events, with no evidence for an increased risk of infection or need for laboratory monitoring. The PALACE pivotal data indicate that apremilast presents a new option for the treatment of PsA that may be appropriate for use early in the treatment ladder. Ongoing PALACE open-label extension trials of up to 4 years will characterize the long-term clinical effects and safety of apremilast therapy. FUNDING: Celgene Corporation, Summit, NJ, USA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40744-014-0005-4) contains supplementary material, which is available to authorized users.